Remnants of the Triglyceride-Rich Lipoproteins, Diabetes, and Cardiovascular Disease - Chait, Alan (Diabetes, 2020)
Diabetes is now a pandemic disease. Moreover, a large number of people with prediabetes are at risk for developing frank diabetes worldwide. Both type 1 and type 2 diabetes increase the risk of atherosclerotic cardiovascular disease (CVD). Even with statin treatment to lower LDL cholesterol, patients with diabetes have a high residual CVD risk. Factors mediating the residual risk are incompletely characterized. An attractive hypothesis is that remnant lipoprotein particles (RLPs), derived by lipolysis from VLDL and chylomicrons, contribute to this residual risk. RLPs constitute a heterogeneous population of lipoprotein particles, varying markedly in size and composition. Although a universally accepted definition is lacking, for the purpose of this review we define RLPs as postlipolytic partially triglyceride-depleted particles derived from chylomicrons and VLDL that are relatively enriched in cholesteryl esters and apolipoprotein (apo)E. RLPs derived from chylomicrons contain apoB48, while those derived from VLDL contain apoB100. Clarity as to the role of RLPs in CVD risk is hampered by lack of a widely accepted definition and a paucity of adequate methods for their accurate and precise quantification. New specific methods for RLP quantification would greatly improve our understanding of their biology and role in promoting atherosclerosis in diabetes and other disorders.